Quel est le but de tout cela ? - Les « causes finales » dans Bouvard et Pécuchet - Atsushi Yamazaki (Flaubert: Revue Critique et Génétique)
The issue of ultimate causes runs through Flaubert’s last novel. This study analyzes the “Causes finales” and “Nihilisme” sequence in chapter VIII, examining not only the “Philosophie” file but also the novel’s drafts, in order to highlight Flaubert’s montage and collage of quotations in his fictionalization of philosophical discourses.